المناخ التنظيمي وعلاقته بالتوافق المهني - عطا الله, محمد (Universty of Eloued جامعة الشهيد حمه لخضر, 2021)
الملخص : هدفت الدراسة التعرف على علاقة المناخ التنظيمي بالتوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي وذلك انطلاقا من التساؤل الرئيسي التالي: ــــ هل توجد علاقة ارتباطيه بين المناخ التنظيمي والتوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي؟ ويندرج تحت هذا التساؤل الأسئلة الفرعية الآتية: - ماهو مستوى المناخ التنظيمي بالمؤسسات التربوية من وجهة نظر أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي يتميز بمستوى مرتفع؟ - ماهو مستوى التوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي يتميز بمستوى مرتفع؟ - هل توجد علاقة ارتباطيه بين المناخ التنظيمي والتوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي؟ - هل توجد علاقة بين أبعاد المناخ التنظيمي والتوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي؟ - أي أبعاد المناخ التنظيمي له أثر مرتفع على التوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي؟ وتماشيا مع طبيعة الموضوع تم الاعتماد على المنهج الوصفي ولجمع بيانات الدراسة تم تطبيق استبياني المناخ التنظيمي والتوافق المهني علي عينة عشوائية منتظمة مقدارها 210 أستاذا وأستاذة من أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي. وقد توصلت الدراسة إلى النتائج التالية: - المناخ التنظيمي لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي يتميز بمستوى منخفض. - التوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي يتميز بمستوى منخفض. - وجود علاقة ارتباطيه بين المناخ التنظيمي والتوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي. - وجود علاقة ارتباطيه بين أبعاد المناخ التنظيمي والتوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي. - بعد علاقات زملاء العمل من أبعاد المناخ التنظيمي له أثر مرتفع على التوافق المهني لدى أساتذة التعليم المتوسط بمقاطعة الرباح ولاية الوادي. Abstract: This study aims at identifying the relationship between the organizational climate and the professional compatibility of middle school teachers in Robbah district in the province of El-Oued (south-east Algeria) based on the following main question: - Is there a relationship between the organizational climate and the professional compatibility of middle school teachers in Robbah districtin the province of El-Oued? The following sub-questions fall under this question: - Is the level of organizational climate high among middle school teachers in Rabbah districtin the province of El-Oued? - Is the level of occupational compatibility high among middle school teachers in Robbah district in the province of El-Oued? - Is there a relationship between the organizational climate and the professional compatibility of middle school teachers in Robbah districtin the province of El-Oued? - Is there a relationship between the organizational climate dimensions and the professional compatibility of middle school teachers in Robbah districtin the province of El-Oued? - Which of the dimensions of the organizational climate has a high impact on the professional compatibility of middle school teachers in Robbah districtin the province of El-Oued? In line with the nature of the topic, the descriptive approach was relied upon, and for collecting the study data, the organizational climate questionnaire, and the professional consensus were applied to a regular random sample of 210 teachers in different middle schools in Rabbah districtin the province of El-Oued. The study has found the following results: - The organizational climate among middle school teachers in Rabbah districtin the province of El-Oued is indeed low. - The professional compatibility of the middle school teachers in Rabbah districtin the province of El-Oued is also low. - There is a correlation between the organizational climate and the professional compatibility of the middle school teachers in Rabbah districtin the province of El-Oued. - There is a correlation between the organizational climate dimensions and the professional compatibility of middle school teachers in Rabbah districtin the province of El-Oued. - The relationship of co-workers from the organizational climate dimensions has a high impact on the professional compatibility of middle school teachers in Rabbah districtin the province of El-Oued.
- دراسة ميدانية لعينة من أساتذة التعليم المتوسط مقاطعة الرباح ولاية الوادي-
أطروحة دكتوراه تخصص تنظيم وعمل في العلوم الإجتماعية
Keywords: المناخ التنظيمي ؛ التوافق المهني؛ ؛ الأساتذة; Organizational climate; Professional compatibility; The teachers